Herbal drugs as therapeutic agents - Amritpal Singh, 1971- (CRC Press, Taylor & Francis Group, 2014)
Phytochemicals are the mainstay of therapeutics of herbal or botanical medicine. Research on phytomolecules is conducted worldwide and several have been screened for clinical trials. This includes several promising anticancer phytomolectules, such as withaferin-a and camphothecin. This book provides a scientific understanding of the mode of action of these molecules. It targets only those phytohemicals and herbal extracts that are subjects of recent pharmacological investigations. Chapters such as industrial crops for steroid manufacturing and anticancer and cytotoxic potential of sesquiter.